As câmeras cinematográficas nos anos 1950/1960 e o cinema brasileiro - Barbuto, Adriano Soriano (Universidade Federal de São Carlos, 2010)
The motion picture cameras have changed through the years. However, they have kept their main design which has not changed during this period. One of the goals of this text is to understand how that design was created, and also the changes it has suffered without losing its essence. Besides that, this text aims to understand how different cameras connected with the Brazilian cinema production in the fifties and sixties. A change on camera s use is noticeable in that period in Brazil. There is a change in appreciation from the more traditional cameras linked to the studio system to the European cameras developed in the thirties and forties, which were lighter and more portable. This issue coincides with a specific characteristic in Brazilian cinema at that time, when people started to believe in the independent cinema production as an answer to the studio system, which was the main thought until then. In order to show this entire context, it has been chosen the Vera Cruz and Cinema Novo, their movies and shootings, to confront and connect them to camera models and their relation to the mode of production
Keywords: Cinema; Cinema brasileiro; Câmeras cinematográficas; Cinematografia; Companhia Cinematográfica Vera Cruz; Cinema Novo; Modo de produção; Brazilian cinema; Motion picture cameras; Cinematography; Mode of production; Vera Cruz; Cinema Novo; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA